Penerapan Data Mining Untuk Menganalisis Kepuasan Pegawai Terhadap Pelayanan Bidang SDM dengan Algoritma C4.5 - Alkhairi, Putrama; Situmorang, Zakarias (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2022)
Employee satisfaction includes the difference between the level of importance and perceived performance or results, and is an alternative evaluation that exceeds employee expectations. There are 5 dimensions to measure service quality based on expectations and perceived performance by employees, namely career development, leadership in HR, policy and law enforcement, building a work atmosphere and providing salaries and rewards. Five dimensions are very influential in the progress of STIKOM Tunas Bangsa, using data mining methods can be found important trends for campuses. Employee satisfaction assessment is based on a questionnaire filled out by the employee. The results of the questionnaire were processed using the c4.5 algorithm. The c4.5 algorithm is a classification method and produces a decision tree. C4.5 turns large facts into decision trees that represent rules. Rules are easy to understand in natural language. Based on the results of the research that has been done, the use of the C4.5 algorithm can help the campus in improving services according to the results of the questionnaire. The results of the calculation, there are two variables satisfied employee questionnaire. Meanwhile, the employee questionnaire was not satisfied with the three variables. The highest gain value is the variable to build a work atmosphere with a value of 0.20619372. The indicator of the variable of building a work atmosphere that has the highest entropy value is a fairly good indicator with a value of 1. The total of questionnaires filled in are 65 questionnaires, 44 people stated they were satisfied and only 21 people said they were not satisfied.